A STANDARDS-BASED EVALUATION OF TEXTBOOK “INTRUCTIONAL MEDIA IN TEACHING ENGLISH TO YOUNG LEARNERS - Fitrian, Novia; Syahid, Abdul; Sumarni (English Teaching Journal and Research: Journal of English Education, Literature, And Linguistics, 2025)
English language teaching in Indonesia faces the challenge of selecting effective learning media that meet the needs of the curriculum. In this context, this study evaluates English learning media using a checklist-based approach designed in accordance with the SNP (Standar Nasional Pendidikan). The evaluation includes an analysis of important aspects such as effectiveness, relevance, accessibility, and compliance with the curiculum. Data were obtained through the collection of various sources, including teaching materials and other evaluation instruments, to assess the extent to which the learning media met the national standards. Through this analysis, this study aims to provide useful insights for the development of more effective learning media as well as assist educators and policy makers in selecting media that support the achievement of English learning objectives. The results of this study are expected to enrich the understanding of instructional media quality in the Indonesian educational environment.